Nodule-associated diazotrophic community succession is driven by developmental phases combined with microhabitat of Sophora davidii - Ai, Jiamin; Yu, Tianfei; Liu, Xiaodong; Jiang, Yingying; Hao, Ziwei; Zhao, Xiaoyu; Wang, Entao; Deng, Zhenshan (Frontiers in Microbiology, 2022)
Aiming at investigating the succession of nodule-endophytic diazotrophs in the developmental phases of root nodule, we performed a high-throughput nifH amplicon sequencing with samples of root nodules and soil associating with Sophora davidii across different phases. The results demonstrated the presence of diverse diazotrophic bacteria and successional community shifting dominated by Mesorhizobium and Bradyrhizobium inside the nodule according to the nodule development. The relative abundance decreased for Mesorhizobium, while decreased first and then increased for Bradyrhizobium in nodule development from young to active to senescent. Additionally, strains M. amorphae BT-30 and B. diazoefficiens B-26 were isolated and selected to test the prominent interaction between them in co-cultured conditions. Under co-culture conditions: B. diazoefficiens B-26 significantly inhibited the growth of M. amorphae BT-30. Intriguingly, growth of B. diazoefficiens B-26 was significantly promoted by co’culture with M. amorphae BT-30 and could utilize some carbon and nitrogen sources that M. amorphae BT-30 could not. We estimated that the competition and cooperation between M. amorphae BT-30 and B. diazoefficiens B-26 was the key driver for the community structure shifting of nodule endosphere diazotrophs. Additionally, the composition of microbial community varied in root nodules, in rhizosphere and in bulk soil, indicating that the environmental filtering differed in the assembly of bacterial communities in these three compartments. The relative abundance of Bradyrhizobium was positively associated with NH4+-N content, and Mesorhizobium was positively correlated with total organic matter (OM) (p < 0.05). Collectively, our study highlights that direct interactions between pairs of bacterial species were responsible for the shift originally observed in the three developmental phases of the S. davidii root nodules.